Human impact on the hydroenvironment of Lake Parishan, SW Iran, through the late Holocene - Jones, Matthew D.; Djamali, Morteza; Holmes, Jonathan; Weeks, Lloyd; Leng, Melanie J.; Lashkari, Arash; Alamdari, Kourosh; Noorollahi, Dariush; Thomas, L.; Metcalfe, Sarah E. (Sage, 2015)
A multiproxy record from Lake Parishan, SW Iran, shows human impact on the lake and its catchment over the last 4000 years. The Parishan record provides evidence of changes in lake hydrology, from ostracod, diatom and isotope analyses, that are directly linked to human activity in the catchment; recorded by pollen and charcoal and supported by regional archaeological and historical data. The lake ostracod fauna is particularly sensitive to human induced catchment alterations and allow us to identify changes in catchment hydrology that are due to more than a simple change in precipitation: evaporation state. Oxygen isotope data from endogenic carbonates follow these faunal changes but also displays a longer trend to more positive values through the period, coincident with regional patterns of water balance for the late Holocene in the eastern Mediterranean.